1. 4 (6 + 7) is the same as (4 • 6) + (4 • 7)
X = 4
2. 6 • 45 = 270
a. 270, (6 • 40) + (6 • 5) = 240 + 30 = 270
b. 210, (6 • 40) - (6 • 5) = 240 - 30 = 210
c. 270, (6 • 50) - (6 • 5) = 300 - 30 = 270
A. 270, C. 270
3. 6m + 7n + 5m - 3n, combine like terms, 6m + 5m = 11m, 7n - 3n = 4n
B. 11m + 4n
4. 2y<u>^3</u> - 4y^2 + y + y<u>^3</u>, exponents tell you what are like terms
C. 2y^3 and y^3
5. 4x<u>^3</u> - 3x^2 + x + 3x<u>^3</u>, combine like terms, then put in descending order
D. 7x^3 - 3x^2 + x
Answer:
19.63
Step-by-step explanation:
To find the area of a circle you can use the formula πr². The diameter (10) is twice the radius. So, the radius is 5. 5² = 25. 25x π =25π. Then you must divide by 4 because the shape is 1/4 a circle.
Hope this helps ;)
Answer:
<u>the conclusion</u>
Step-by-step explanation:
The final paragraph of an informational essay or article is called <u>the conclusion</u>.
1.) (x+2) (x+4) (x-4)
2.) (3x-4) (x^2 +3)
3.) 2x(2x-5) (x-4)
4.) (4x+3) (2x^2 +1)
5.) (4x-5) (16x^2 + 20x+25)
6.) (x+2) (x-2) (x^2+3)
7.) 2x^2(2x+3) (4x^2-6x+9)
8.). (4x-1) (x+1) (x-1)
*Hope this helped, good luck :-)
Answer:C
Step-by-step explanation:
because if x 1/2 to (6x+12) it give you = 6x+13